Using a Conflict Framework Analysis to Help Beekeepers and Giant Armadillos (Priodontes maximus) Coexist - Catapani, Mariana L.; Morsello, Carla; Oliveira, Bruna; Desbiez, Arnaud L. J. (Frontiers in Conservation Science, 2021)
Damage caused by wildlife is one reason preventing peaceful coexistence between humans and wildlife. To identify the complexity and scope of human-wildlife interactions and to guide conservation interventions, a theoretical framework has been recently proposed, based on the field of conflict analysis and peacebuilding. Despite its importance, to our knowledge, there are no studies yet testing the framework. We therefore adapted and expanded the framework to investigate a wildlife-people interaction scenario, involving damage by giant armadillos (Priodontes maximus) to apiaries in the Brazilian Cerrado biome of Mato Grosso do Sul state. From August to November 2018, we interviewed 111 beekeepers identified through a mixed random and snowball sampling design to assess at which level of conflict this interaction could be framed, and to identify strategies able to promote coexistence. Analysis of the five key areas of the framework suggested the current human-wildlife interaction is a level one conflict. This means the negative relation between beekeepers and giant armadillos is still not rooted in less visible, more complex social disagreements, but founded in a material dispute: destruction of beehives. We used the findings to create an intervention strategy which involves: (i) the implementation of mitigation strategies that prevent giant armadillos from predating beehives; (ii) a certification scheme to acknowledge beekeepers’ efforts to implement the mitigation strategies, and (iii) the devise of a Citizen Science Program using an app that enables data gathering for adaptive management, as well as maintains beekeeper engagement. We hope beekeepers-giant armadillos’ coexistence will become beneficial rather than a challenge with the novel interventions.